Changes in COVID‐19 measures in the workplace: 8‐month follow‐up in a cohort study of full‐time employees in Japan. Issue 1 (14th September 2021) - Asaoka, Hiroki; Sasaki, Natsu; Imamura, Kotaro; Kuroda, Reiko; Tsuno, Kanami; Kawakami, Norito
Abstract: Objectives: It is unclear how many workplace COVID‐19 preventive measures were maintained during repeated outbreaks. The aim of this study was to investigate a longitudinal change of implementation of workplace preventive measures responding to COVID‐19 in Japan. Methods: An online longitudinal study was conducted using a cohort of full‐time employees in Japan, starting in March 2020 (T1), with follow‐up surveys in May (T2), August (T3), and November (T4) 2020. A repeated measures analysis of variance was performed to compare the difference among the four surveys in the mean number of 23 predetermined items of the measures implemented. Results: The final sample comprised 800 employees. The mean number of the implemented measures increased from T1 to T2, but did not change from T2 to T3, then decreased from T3 to T4. The number of workplace preventive measures significantly increased from T1 to T2 for 21 items ( P < .001), and significantly decreased from T3 to T4 for 14 items ( P < .001 to P = .005). Conclusions: While the preventive measures responding to COVID‐19 in the workplace were well‐implemented during the earlier phase of the outbreak, they seem to have been relaxed after a huge outbreak (T3 to T4: August to November 2020). Workplaces should be encouraged to continue the preventive measures over repeated outbreaks.